2022-RA-420-ESGO Treatment and outcome of patients with high-grade advanced ovarian cancer (AOC) – real world data of the german quality assurance project (QS Ovar of the AGO Study Group). (20th October 2022) - Mahner, Sven; Bois, Andreas du; Pfisterer, Jacobus; Hilpert, Felix; Kerkmann, Markus; Sehouli, Jalid; de Gregorio, Nikolaus; Hanker, Lars Ch; Heitz, Florian; Marmé, Frederik; Wölber, Linn Lena; Holtmann, Laura; et al.
Abstract : Introduction/Background: Outcome of patients with AOC depends largely on treatment quality and expertise of treating physicians and centers. To assess treatment reality and quality in Germany, we initiated a nationwide quality assurance program. Methodology: All German hospitals treating patients with AOC were asked to document their patients with primary diagnosis in the third quarters of 2012 and 2016 in a central database. The current analysis focuses on patients with high-grade AOC stage III/IV. Results: In total, 1010 patients with high-grade AOC were documented. This represents 63% of all patients diagnosed in Germany. Median age was 65 years. The majority (774/1010 – 76.6%) were diagnosed with stage III disease and 947/1010 (93.8%) had serous, 34 (3.4%) endometrioid and 29 (2.9%) clear cell histology. 915/1010 (90.6%) had primary debulking surgery (PDS). Complete resection was achieved in 434/915 (47.4%) at PDS and in 54/95 (56.8%) at interval debulking surgery (IDS). Median PFS and OS in patients with PDS and complete resection was 29.7 and 63.1 months compared to 16.8 and 30.7 months in patients with residual disease (PFS: HR 0.46, 95% CI 0.37–0.54 and OS: HR 0.37, 95% CI 0.31–0.45). First-line chemotherapy was carboplatin/paclitaxel (TC) in 919/1010 (91%) of the patients, 627 (62%) also received bevacizumab (TCB) and 544 of these (87%) also received bevacizumab maintenance therapy. Median PFS and OS with TCB was 23.3 and 46.2 months and 18.5 and 39.0 months with TC (PFS: HR 0.86, 95% CI 0.73–1.01 and OS: HR 0.79, 95% CI 0.66–0.95). The rate of complete tumor resection at surgery as well as the use of bevacizumab increased between the two periods. Conclusion: The majority of patients were treated with primary surgery followed by TCB. Outcome was best when complete tumor resection was achieved at primary surgery and patients received combination chemotherapy with maintenance treatment.